2021
DOI: 10.1371/journal.pone.0246685
|View full text |Cite
|
Sign up to set email alerts
|

Invasive species allelopathy decreases plant growth and soil microbial activity

Abstract: According to the ‘novel weapons hypothesis’, invasive success depends on harmful plant biochemicals, including allelopathic antimicrobial roots exudate that directly inhibit plant growth and soil microbial activity. However, the combination of direct and soil-mediated impacts of invasive plants via allelopathy remains poorly understood. Here, we addressed the allelopathic effects of an invasive plant species (Rhus typhina) on a cultivated plant (Tagetes erecta), soil properties and microbial communities. We gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 35 publications
2
49
0
2
Order By: Relevance
“…Invasive weed species have the potential to release allelopathic substances to the surrounding environments to suppress their neighboring competing plants [ 11 , 12 , 13 , 14 , 15 ]. Parthenium hysterophorus L. has taken the shape of a noxious weed and is becoming a threat to crop production, animal husbandry and human health due to its strong allelopathic effects [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Invasive weed species have the potential to release allelopathic substances to the surrounding environments to suppress their neighboring competing plants [ 11 , 12 , 13 , 14 , 15 ]. Parthenium hysterophorus L. has taken the shape of a noxious weed and is becoming a threat to crop production, animal husbandry and human health due to its strong allelopathic effects [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid pace of IAPs infestation in the Anthropocene perturbed the biotic and abiotic components of the environment (El-Barougy et al 2021;Rathee et al 2021). To this end, the IAPs have driven the environmental degradation by changing nutrient and pollutant cycling, habitat structure, microbial diversity; hydro-morphology, soil chemistry, water and disturbance regimes (Pyšek et al 2020;Qu et al 2021). In contrast, Gao et al (2020) studied the effects of soil attributes on IAPs and revealed that soil nutrient heterogeneity has driven the growth of plant invaders.…”
Section: Physico-chemical and Allelochemic Attributesmentioning
confidence: 99%
“…Several IAPs such as Eichhornia crassipes and Salvinia molesta can adversely influence the productivity of paddy fields (Kariyawasam et al 2021). Allelochemic compounds released from IAPs (e.g., Rhus typhina) adversely influenced the growth of cultivated plant such as Tagetes erecta (Qu et al 2021). Furthermore, IAPs in concert with climate change have remarkably affected the global agricultural systems (Ziska et al 2011;Paini et al 2016) and hence impose adverse implications on food security.…”
Section: Physico-chemical and Allelochemic Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the challenges of globalization is biotic exchange (Reaser et al, 2007). Occurring at increasing rates and volumes, the consequences of invasive species dispersed beyond their natural barriers often harm native biodiversity and impair different functions of socio-biological systems (Sala et al, 2000;Walsh et al, 2016;Qu et al, 2021). Yet, impacts of concurrent multiple invasions remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%